Effect of Approach Play With Finger Painting on Social Interaction Ability among Autism Childrens’s - Henni Marina Siregar; Rian Yuliyana; Khusnul Khatimah (Alma Ata University Press, 2017)
Autism is a complex developmental disorder. Autism has some disturbances in the areas of speech, communication, and social interaction. Some treatments can be done such as behavior therapy, play therapy and speech therapy, one of treatment is approach play with finger painting. Finger painting is a painting technique uses finger directly without tools and brush. Finger painting can be used as a play tool and can train to develop a high sense of solidarity. The aim of this study was to analyze the effect of approach play with finger painting on autism children’s social interaction in SLB Mutiara Tanjungpinang. Method of this research was used quasi-experiment design with pretest dan posttest without control group approach. the sample was 7 children between 6 and 12 years old using total sampling design. This study was conducted at Sekolah Luar Biasa Mutiara Tanjungpinang. Data collected by observation of ATEC (Autism Treatment Evaluation Checklist) modification. Data were analyzed with Wilcoxon Match Pair Test. The results showed that ρ value=0.025 (ρ value <ɑ=0.05). The result of this study concluded that there was an effect of approach play with finger painting on autism children’s social interaction in SLB Mutiara Tanjungpinang. Based on the result, it is recommendation for educational health institution and special school to applied finger painting method to exercise the autism children’s social interaction.